The Effect of Ankle Balance Taping with Elastic Tape on Dynamic Balance and Round Kick Performance in Youth’s Taekwondo Athletes - Chotirat, Pinyo; Eungpinichpong, Wichai (Journal for Developing the Social and Community, 2023)
The purpose of this study was to examine the effect of ankle taping with elastic tape on dynamics balance and round kick performance in youth’s taekwondo players. Eighteen blackbelt youth’s taekwondo players from taekwondo club Pattani province, volunteered to participated in this study. They were volunteer age between 12 -15 years old, there were healthy and not ankle injury. The participants were divided into elastic tape as experiment group and no -tape as control group 9 people in each group. After that participants in both groups underwent dynamic balance using star excursion balance test and round kick performance on round kick performance and high round kick then moved participant to rest room, after this randomized to treat and test, when completed on both group research assistant was record data. Researcher used Man – Whitney U test to compare between group with elastic tape and no tape on dynamic balance and round kick performance. The result revealed that on round kick performance, ankle taping group was significant improvement than non - taping group in round kick repeat and high round kick on post intervention (p<0.05). In addition, there were a significant difference in post intervention between taping group and non-taping group on 7 directions consist of anterior, anteromedial, medial, posteromedial, posterior, posterolateral, lateral was significantly different. Whereas, there was not significant difference in anterolateral direction. In this preliminary study, the findings could be concluded an elastic tape was apply on ankle that demonstrated immediate effect preservation on postural control, while round kick repeated and height round kick.